Perceptions of professionals interested in accounting and auditing about acceptance and adaptation of global financial reporting standards - Bozkurt, Orhan (2013)
Nowadays, one of the final aims of the institutions working on transparency and standardization of financial statements, and the publication of standards related to the profession of accounting & auditing has been to put into practice a uniform global set of standards which will be applicable in finance. Before 2000, in the case of a preference between IFRS & US GAAP regarding which should be internationally accepted uniform set of application, world public opinion used to accept U.S. Generally Accepted Accounting Principles (US GAAP) as reference. Today, great majority of the world takes IFRS as a reference. This study contains evaluations related to the results of research on the thoughts & perceptions of the professionals interested in accounting and auditing about application and development of international financial reporting standards as national financial reporting standards. As a result of the research, it was determined that those interested in accounting and auditing see significant advantages in the application of IFRS. Accountants and auditors think that in case IFRS is applied, comprehensibility and reliability of financial statements shall increase, at the same time accounting frauds shall decrease. DOI: 10.1016/S2077-1886(13)70019-2